Assessment of Selected Social Economic Factors Affecting Sugarcane Productiivity Among Small Scale Farmers in West Kabras Ward, Malava Constituency - Imbusi, Muhonja Margaret (University of Embu, 2020)
Sugarcane is a cash crop that is grown in Kenya by both small scale and large farmers. It is mainly grown to enhance incomes of farmers which improve their living standards. The relevance of this study was to determine the effect of social economic factors on sugarcane productivity among small scale farmers in West Kabras Ward, Malava constituency. The specific objectives were; the effect of land size and the effect of input cost accessibility on sugarcane productivity in west Kabras, Malava constituency. This study used cross-sectional design. Simple random sampling was used to collect primary data from a sample size of 30 small scale farmers using questionnaires. Data was analyzed in SPSS. Regression analysis model (multiple regression) was used to determine the effect of the independent variables on the dependent variable. Findings were statistically significant to the study. The study however recommended that the company in partnership with other sugarcane stakeholders should come up with policies and implement them to enhance the productivity of sugarcane in west Kabras Ward for the benefits of small scale farmers.